Customer Satisfaction with Loan Service for Agricultural Production: A Case Study at Agriculture and Rural Development Bank in Nam Dinh province of Vietnam - Thi, Hai Ninh Nguyen (Discoveries in Agriculture and Food Sciences, 2025)
Agriculture and Rural Development bank plays a crucial role in loan service for agricultural production and farm households’ economic development in Vietnam. This study evaluates customer satisfaction with loan services at Agribank in Nam Dinh province of Vietnam, focusing on factors such as interest rates, loan procedures, loan availability, bank staff competence, and facilities. Using surveyed data from 210 customers who are farmers borrowing capital for agricultural production, the research results show that interest rates and capital responsiveness have the most significant impact on customer satisfaction, with high levels of contentment. However, loan procedures and facilities still do not meet high satisfaction standards. This study also reveals that staff competence and limitations in loan processes hinder the timely and efficient service of customers. Based on these findings, the study suggests solutions to improve loan procedures, enhance staff training, and upgrade the bank’s facilities to increase customer satisfaction and help the bank maintain competitiveness in the current banking environment in Vietnam.